The Magnitude of Postconvulsive Leukocytosis Mirrors the Severity of Periconvulsive Respiratory Compromise: A Single Center Retrospective Study - Vega, Jose L.; Emmady, Prabhu; Roels, Christina; Conforti, John; Ramirez, Catalina; Dorak, Mehmet T. (Frontiers in Neurology, 2019)
Background: Generalized epileptic convulsions frequently exhibit transient respiratory symptoms and non-infectious leukocytosis. While these peri-ictal effects appear to arise independently from one another, the possibility that they stem from a common ictal pathophysiological response has yet to be explored. We aimed to investigate whether peri-ictal respiratory symptoms and postictal leukocytosis coexist. Methods: We performed a single center retrospective chart review of 446 patients brought to our emergency department between January 1, 2017 and August 23, 2018 for the care of generalized epileptic convulsions with or without status epilepticus. We included 152 patients who were stratified based on the presence (PeCRC+) or absence (PeCRC–) of overt periconvulsive respiratory compromise (PeCRC). In addition, patients were stratified based on the presence or absence of postconvulsive leukocytosis (PoCL), defined as an initial postconvulsive white blood cell (WBC) count ≥ 11,000 cells/mm3. Triage vital signs, and chest x ray (CXR) abnormalities were also examined. Results: Overt PeCRC was observed in 31.6% of patients, 43% of whom required emergent endotracheal intubations. PoCL was observed in 37.5% of patients, and was more likely to occur in PeCRC+ than in PeCRC– patients (79.2% vs 18.2%; OR = 17.0; 95% CI = 7.2 to 40.9; p<0.001). Notably, the magnitude of PoCL was proportional to the severity of PeCRC, as the postconvulsive WBC count demonstrated a negative correlation with triage hemoglobin oxygen saturation (R = –0.22; p<0.01; CI = –0.48 to –0.07). Moreover, a receiver operating characteristic analysis of the WBC count’s performance as predictor of endotracheal intubation reached a significant area under the curve value of 0.81 (95% CI = 0.71 – 0.90; p<0.001). Finally, PeCRC+ patients demonstrated frequent CXR abnormalities, and their postconvulsive WBC counts correlated directly with triage heart rate (R=0.53; p<0.001). Conclusion: Our data support the existence of an ictal pathophysiological response, which induces proportional degrees of PoCL and PeCRC. We suggest this response is at least partially propelled by systemic catecholamines.